INVESTIGATION AUTHORITIES OF FINANCIAL SERVICES AUTHORITY IN SYARIAH BANKING - Hamsir Hamsir (Jurnal Dinamika Hukum, 2015)
This paper aims to explore the authority of the FSA as one of the institutions that deal with crime investigation in banking institutions, especially in Islamic Banking. Investigators FSA has great authority other than the authority to conduct investigations that are not owned by other investigators. The existence of this authority would lead to overlapping investigation with a given investigation agencies such as the police and the prosecutor. Fundamental problems are experienced by the FSA in conducting the investigation is less availability of human resources of FSA investigator. Therefore, inevitably required cooperation with the Police in effecting the FSA investigation. Effectiveness of investigations conducted by the FSA task for banking crimes that occurred in Islamic Banking is need synergy of communication and coordination with the DSN as an institution authorized by the Islamic Banking Act to provide recommendations to other agencies including the FSA if there is suspicion of a criminal offense in Islamic Banking.Key words: financial service authority; investigation; syariah banking